CFD investigation of interaction effect between hull and accommodation on wind drag of a container ship in head wind - Ngo Van, He; Truong Van, Thuan (Vietnam Journal of Marine Science and Technology, 2021)
In this paper, we present a research on applying a commercial Computational Fluid Dynamics (CFD) code to determine interaction effect between hull and accommodation on wind drag of a container ship. For the high superstructure and large windward area ships such as container, wind drag acting on hull accounts for a large amount of total resistance. To clearly find aerodynamic performance and interaction effects on wind drag of a container ship, a full scale 1,200 TEU container has been used as a reference model. From results of comparison in the two computed cases of hull with and without accommodation, the interaction effects between hull and accommodation on aerodynamic performance and wind drag have been investigated. The targets of the paper has proposed a new solution to improve aerodynamic performances and reduce wind drag acting on the ship by reducing interaction effects between hull and accommodation.